Auto-Backlund transformation and similarity reductions for coupled Burger's equation - Inan, Ibrahim E.; Kaya, Dogan; Ugurlu, Yavuz (Elsevier Science Inc, 2010)
In this work, we applied Backlund transformation and similarity reduction for coupled Burger's equation. Clarkson and Kruskal developed a direct and simple method to obtain more similarity solutions of nonlinear partial differential equation. We received our inspiration from Fan's article, as far as we think that our work is an extended one from the Fan's has done in his paper. As a result of this study, we obtained solitary wave solutions and traveling wave solutions of coupled Burger's equation. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Backlund transformation; Similarity reduction; Coupled Burger's equation; Solitary wave solution; Traveling wave solution